A biomechanical analysis of traumatic brain injury for slips and falls from height. (January 2019) - Post, Andrew; Taylor, Karen; Hoshizaki, T Blaine; Brien, Susan; Cusimano, Michael D; Marshall, Shawn
Background: Falls are a common cause of morbidity and mortality in society, particularly among the aged and young. There has been research to describe the epidemiology of these types of events, but to date there has been few correlations of clinical brain injury outcomes and metrics used in biomechanical research; parameters often used to help develop protective devices and environments. The purpose of this research was to examine the kinematic characteristics of falls from standing and higher heights in an effort to understand how clinical brain injury is predicted by biomechanical injury metrics. Methods: Computer simulations of nine traumatic brain injury events from falling were conducted to determine the biomechanical metrics associated with each injury case. Results: Many of the impacts were to the occipital region of the head, as would be expected from backward falls or from slipping from ladders. These falls resulted in low rotational acceleration values and high linear accelerations, suggesting linear acceleration may be an important characteristic of this injury mechanism. In addition, even though each case resulted in severe head injury, the HIC15 (Head Injury Criterion) values did not consistently predict injury when the kinematic output was lower than 300 g. This result suggests that HIC15 may have limited value as a predictor for high energy short duration direct impacts to the head. The results supported a relationship between fall height and duration of loss of consciousness, with the higher fall heights producing longer times of unconsciousness. Conclusion: Linear acceleration may be the metric that should be focused on to develop further strategies to protect against severe TBI for fall cases similar to those in this research. In addition, the HIC15 may not be suitable as a predictive metric for TBI and future development of protective devices for the prevention of head injury should take this into account.